A polyethylene flash-spun nonwoven fabric with uniform thickness

By using a reverse electrostatic device to adsorb the wire mesh in the spinning process, the problem of uneven thickness during flash spinning is solved, and the uniformity of polyethylene flash spinning non-woven fabrics and excellent breathability and moisture absorption properties are achieved.

CN116334836BActive Publication Date: 2025-03-04JIANGSU QINGYUN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211238142.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2022-10-10
Publication Date
2025-03-04
Estimated Expiration
2042-10-10

AI Technical Summary

Technical Problem

During the flash spinning process, the steam generated causes uneven thickness of the spinning product, affecting the uniformity and performance of the product.

Method used

By introducing a reverse electrostatic device in the spinning process, the wire mesh is adsorbed by an electrostatic field, reducing the wire mesh being disturbed by airflow, ensuring uniform drop of the wire mesh, thereby improving the thickness uniformity of the product.

Benefits of technology

The thickness uniformity of polyethylene flash spun non-woven fabric is achieved, the uniformity of the product is improved, the Glair breathable resistance is reduced, and the moisture absorption expansion rate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334836B_ABST
    Figure CN116334836B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyethylene flash-spun nonwoven fabric with uniform thickness, wherein the weight of the polyethylene flash-spun nonwoven fabric is greater than 50 g / m 2 ; The thickness of the polyethylene flash spun nonwoven fabric is 0.1-0.3 mm; the area of ​​the polyethylene flash spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] accounts for more than 60% of the total area of ​​the polyethylene flash spun nonwoven fabric; the hygroscopic expansion rate of the polyethylene flash spun nonwoven fabric is 0.5%-0.8% when the relative humidity is between 33% and 84%. The polyethylene flash nonwoven fabric of the present invention has a uniform texture and good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile production, and relates to a polyethylene flash-spun nonwoven fabric, in particular to a polyethylene flash-spun nonwoven fabric with uniform thickness. Background Art

[0002] The flash spinning process produces a large amount of solvent vapor along with the production of the wire mesh during the spinning process. The large amount of vapor produced will generate a strong wind field near the spinning components due to the pressure difference. Since the spun wire mesh is light in weight and has a large specific surface area, it will be driven by the airflow to fly. Especially when multiple spinnerets are used for production, the airflows will affect each other. Such "flying" will have a great impact on the uniformity of the product. Summary of the invention

[0003] The purpose of the present invention is to provide a polyethylene flash-spun nonwoven fabric with uniform thickness in view of the above problems;

[0004] The invention creatively provides a polyethylene flash-spun nonwoven fabric with uniform thickness, the raw material of which comprises polyethylene.

[0005] The weight of polyethylene flash spun nonwoven fabric is greater than 50g / m 2 ;

[0006] The thickness of polyethylene flash spun nonwoven fabric is 0.1 to 0.3 mm;

[0007] The area of ​​polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] accounts for more than 60% of the total area of ​​polyethylene flash-spun nonwoven fabric;

[0008] The hygroscopic expansion rate of polyethylene flash-spun nonwoven fabric is 0.5% to 0.8% when the relative humidity is between 33% and 84%.

[0009] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the area of ​​the polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] accounts for more than 70% of the total area of ​​the polyethylene flash-spun nonwoven fabric.

[0010] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the area of ​​the polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] accounts for more than 80% of the total area of ​​the polyethylene flash-spun nonwoven fabric.

[0011] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the weight of the polyethylene flash-spun nonwoven fabric is 60 to 75 g / m 2 .

[0012] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the weight of the polyethylene flash-spun nonwoven fabric is 75 to 85 g / m 2 .

[0013] In the polyethylene flash-spun nonwoven fabric with uniform thickness, the hygroscopic expansion rate of the polyethylene flash-spun nonwoven fabric is 0.65% to 0.75% when the relative humidity is between 33% and 84%.

[0014] In the polyethylene flash-spun nonwoven fabric with uniform thickness, the hygroscopic expansion rate of the polyethylene flash-spun nonwoven fabric is 0.7% when the relative humidity is between 33% and 84%.

[0015] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the Gurley air permeability resistance of the polyethylene flash-spun nonwoven fabric is 10 to 50 seconds.

[0016] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the Gurley air permeability resistance of the polyethylene flash-spun nonwoven fabric is 14 to 25 seconds.

[0017] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the polyethylene flash-spun nonwoven fabric has a Gurley air permeability resistance of 20 seconds.

[0018] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the Gurley air permeability resistance of the polyethylene flash-spun nonwoven fabric is 25 to 35 seconds.

[0019] In the above-mentioned polyethylene flash-spun nonwoven fabric with uniform thickness, the Gurley air permeability resistance of the polyethylene flash-spun nonwoven fabric is 35 to 45 seconds.

[0020] Geller resistance is measured by the time it takes for 100 ml of gas to pass through.

[0021] The processing method of the polyethylene flash-spun nonwoven fabric with uniform thickness comprises the following steps:

[0022] (1) The spinning solution is ejected through the nozzle, and the solvent in the spinning solution evaporates instantly. While the polymer solute in the spinning solution cools and solidifies into a continuous wire mesh, the steam formed by the evaporation of the solvent falls onto the conveyor belt in the web forming area together with the wire mesh under the guidance of the windshield;

[0023] (2) The screen is adsorbed on the conveyor belt through the reverse electrostatic field of the reverse electrostatic device;

[0024] (3) The screen is conveyed to the subsequent process section via a conveyor belt to obtain a polyethylene flash nonwoven fabric.

[0025] The reverse electrostatic device can reduce or even eliminate the disturbance of the screen caused by the airflow, greatly improving the uniformity of the product.

[0026] In the above processing method, the spinning solution contains a spinning solvent and a polymer solute, wherein the mass fraction of the polymer solute in the spinning solution is 7 to 18%.

[0027] The polymer solute is polyethylene.

[0028] The spinning solvent is one or a mixture of two or more of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, ketones, nitriles, amides, fluorocarbons, sulfur dioxide, carbon disulfide, nitromethane, and water.

[0029] In the above processing method, the reverse electrostatic device is located below each nozzle.

[0030] In the above processing method, the reverse electrostatic device includes an electrostatic generator and an electrostatic plate connected to the electrostatic generator through a wire.

[0031] The electrostatic generator generates an electrostatic field on the electrostatic plate that is opposite to the charge of the screen.

[0032] In the above processing method, the plane of the electrostatic plate is parallel to the surface of the conveyor belt in the screen conveying area.

[0033] In the above processing method, the distance between the electrostatic plate and the lower surface of the conveyor belt is 25 to 150 mm, preferably 40 to 60 mm, and most preferably 50 mm.

[0034] By setting the appropriate distance between the electrostatic plates, it is possible to ensure that the electrostatic plates can function and the thickness is uniform, thereby ensuring that the breathability resistance of the Ge Lai Er is small and the moisture absorption expansion rate is large.

[0035] In the above processing method, an electrostatic plate is arranged under each nozzle, the vertical center line of the electrostatic plate is aligned with the vertical line of the screen, the width is greater than 500mm, the length is less than the width of the conveyor belt, and the horizontal distance between the two edges and the edge of the conveyor belt is 25 to 100mm, preferably 50mm.

[0036] The center line of the electrostatic plate plane is aligned with the vertical line of the screen to avoid flying wires, thereby avoiding serious uneven thickness and ensuring that the breathability resistance and moisture absorption expansion rate of the Grayer are in the best state.

[0037] In the above processing method, there is a whole electrostatic plate under each nozzle, that is, the vertical projection surface of the electrostatic plate covers all the spinning components, and the distance between the left and right sides of the electrostatic plate and the edge of the conveyor belt is greater than 25 mm.

[0038] In the above processing method, in step (2), the conveyor belt passes through the electrostatic release component to release static electricity and then enters the mesh forming area to receive the screen. The screen is adsorbed on the conveyor belt by the reverse electrostatic field of the reverse electrostatic device.

[0039] Compared with the prior art, the advantages of the present invention are:

[0040] The polyethylene flash nonwoven fabric of the invention has uniform texture and good application prospect.

[0041] The polyethylene flash nonwoven fabric of the present invention has a smaller Geller air permeability resistance and a larger hygroscopic expansion rate, and can ensure the air permeability effect and water absorption capacity.

[0042] The present invention improves the uniformity of the product by optimizing the spinning process. Specifically, an electrostatic field with an opposite charge to that of the wire mesh is added where the wire mesh falls, and the wire mesh is adsorbed on the conveyor belt through the Coulomb force, thereby reducing or even eliminating the "flying" of the wire mesh caused by the airflow, thereby improving the uniformity of the product, the Geller air permeability resistance and the hygroscopic expansion rate.

[0043] The present invention can ensure that the electrostatic plates play a role and have uniform thickness by setting a suitable distance between the electrostatic plates, thereby ensuring that the Geller air permeability resistance is small and the moisture absorption expansion rate is large.

[0044] The center line of the electrostatic plate plane of the present invention is aligned with the vertical line of the screen, so as to avoid the occurrence of flying wires, thereby avoiding serious uneven thickness, and further ensuring that the Geller air permeability resistance and moisture absorption expansion rate reach the optimal state. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention provides a process flow chart of a polyethylene flash-spun nonwoven fabric with uniform thickness.

[0046] In the figure: spinning component 1, screen channel 11, nozzle 12, wind shield 13, conveyor belt 21, web forming area 23, reverse electrostatic device 3, electrostatic generator 31, conductor 32, electrostatic plate 33, electrostatic discharge component 5, discharge brush 51, discharge sheet fixing box 52. DETAILED DESCRIPTION

[0047] Further described by the following specific examples;

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0049] Example 1

[0050] like Figure 1 As shown, a process for producing polyethylene flash-spun nonwoven fabrics with uniform thickness comprises the following steps:

[0051] S1 uses polyethylene as a polymer solute and a mixture of dichloromethane, trichloromethane, 2,3-dihydrodecafluoropentane, and 1H,6H-perfluorohexane in a mass ratio of 4:4:1:1 as a spinning solvent. The polymer solute and the spinning solvent are mixed to prepare a spinning solution with a polymer solute content of 9wt%.

[0052] S2 sprays the spinning solution through four groups of nozzles 12. Windshields 13 are arranged on both sides below the discharge port of each group of nozzles 12. The windshields 13 on both sides are arranged opposite to each other along the transmission direction of the wire mesh, and there is a wire mesh channel 11 between the windshields 13 on both sides to provide a space for the wire mesh to fall vertically. The solvent in the spinning solution evaporates instantly after being sprayed. While the polymer solute in the spinning solution cools and solidifies into a continuous wire mesh, the steam formed by the evaporation of the solvent falls onto the conveyor belt 21 of the web forming area 23 together with the wire mesh under the guidance of the windshield 13.

[0053] S3 The conveyor belt 21 releases static electricity through the electrostatic discharge component 5 and enters the web forming area 23 to receive the screen. The screen is adsorbed on the conveyor belt 21 by the reverse electrostatic field of the reverse electrostatic device 3.

[0054] The conveyor belt 21 is arranged horizontally in the web forming area 23. The reverse electrostatic device 3 includes an electrostatic generator 31 and an electrostatic plate 33 connected to the electrostatic generator 31 through a wire 32 and parallel to the surface of the conveyor belt 21 in the screen transmission area 23. The electrostatic plate 33 is arranged below the screen forming area 23 of the conveyor belt 21. The wire 32 is a high-voltage wire coated with silicone rubber. The electrostatic plate 33 is 30 mm away from the lower surface of the conveyor belt 21 in the screen forming area 23. Four electrostatic plates 33 are arranged along the screen transmission direction, each electrostatic plate 33 corresponds to a screen channel 11, and the projection surface of the electrostatic plate 33 in the vertical direction covers the screen channel 11. The width of the electrostatic plate 33 along the screen transmission direction is 600 mm, the distance between the electrostatic plate 33 and the edge of the conveyor belt 21 is 30 mm, and the central vertical line of the electrostatic plate 33 coincides with the vertical line of the screen falling in the screen channel 11. Thereby ensuring the effect of the electrostatic plate 33 on the screen.

[0055] An electrostatic discharge component 5 is arranged at a position 500 mm from the center line of the first screen channel 11 at the upstream end of the conveying direction of the conveyor belt 21. The electrostatic discharge component 5 includes discharge brushes 51 densely distributed perpendicular to the screen conveying direction, and a discharge sheet fixing box 52 for fixing the discharge brushes 51. The discharge brushes 51 are in contact with the surface of the conveyor belt 21 through elasticity or self-weight, and the discharge brushes 51 are in contact with the upstream end of the web forming area 23. The discharge brushes 51 are electrically connected to the discharge sheet fixing box 52, and the discharge sheet fixing box 52 is grounded through a circuit.

[0056] The S4 screen is conveyed to the subsequent process section via a conveyor belt 21 to obtain a polyethylene flash nonwoven fabric.

[0057] Example 2

[0058] This embodiment is basically the same as Embodiment 1, except that:

[0059] The polymer solute in S1 is mixed with the spinning solvent to prepare a spinning solution with a polymer solute content of 10 wt%.

[0060] In S3, the distance between the electrostatic plate 33 and the lower surface of the conveyor belt 21 in the web forming area 23 is 60 mm. Four electrostatic plates 33 are arranged along the direction of screen transmission, each electrostatic plate 33 corresponds to a screen channel 11, and the projection surface of the electrostatic plate 33 in the vertical direction covers the screen channel 11. The width of the electrostatic plate 33 along the direction of screen transmission is 700 mm, and the distance between the electrostatic plate 33 and the edge of the conveyor belt 21 is 45 mm. The center line of each electrostatic plate 33 in the width direction coincides with the vertical line of the screen falling in the screen channel 11 in the vertical plane.

[0061] Example 3

[0062] This embodiment is basically the same as Embodiment 1, except that:

[0063] The polymer solute in S1 is mixed with the spinning solvent to prepare a spinning solution with a polymer solute content of 11 wt%.

[0064] In S3, the distance between the electrostatic plate 33 and the lower surface of the conveyor belt 21 in the web forming area 23 is 90 mm. Four electrostatic plates 33 are arranged along the direction of screen transmission, each electrostatic plate 33 corresponds to a screen channel 11, and the projection surface of the electrostatic plate 33 in the vertical direction covers the screen channel 11. The width of the electrostatic plate 33 along the direction of screen transmission is 800 mm, and the distance between the electrostatic plate 33 and the edge of the conveyor belt 21 is 60 mm. The center line of each electrostatic plate 33 in the width direction coincides with the vertical line of the screen falling in the screen channel 11 in the vertical plane.

[0065] Example 4

[0066] This embodiment is basically the same as Embodiment 1, except that:

[0067] The polymer solute in S1 is mixed with the spinning solvent to prepare a spinning solution with a polymer solute content of 12 wt %.

[0068] In S3, the distance between the electrostatic plate 33 and the lower surface of the conveyor belt 21 in the web forming area 23 is 120 mm. Four electrostatic plates 33 are arranged along the direction of screen transmission, each electrostatic plate 33 corresponds to a screen channel 11, and the projection surface of the electrostatic plate 33 in the vertical direction covers the screen channel 11. The width of the electrostatic plate 33 along the direction of screen transmission is 900 mm, and the distance between the electrostatic plate 33 and the edge of the conveyor belt 21 is 75 mm. The center line of each electrostatic plate 33 in the width direction coincides with the vertical line of the screen falling in the screen channel 11 in the vertical plane.

[0069] Example 5

[0070] This embodiment is basically the same as Embodiment 1, except that:

[0071] The polymer solute in S1 is mixed with the spinning solvent to prepare a spinning solution with a polymer solute content of 13 wt %.

[0072] In S3, the distance between the electrostatic plate 33 and the lower surface of the conveyor belt 21 in the web forming area 23 is 150 mm. Four electrostatic plates 33 are arranged along the direction of screen transmission, each electrostatic plate 33 corresponds to a screen channel 11, and the projection surface of the electrostatic plate 33 in the vertical direction covers the screen channel 11. The width of the electrostatic plate 33 along the direction of screen transmission is 1000 mm, and the distance between the electrostatic plate 33 and the edge of the conveyor belt 21 is 100 mm. The center line of each electrostatic plate 33 in the width direction coincides with the vertical line of the screen falling in the screen channel 11 in the vertical plane.

[0073] Comparative Example 1

[0074] This embodiment is basically the same as Embodiment 3, except that:

[0075] In S3, the distance between the electrostatic plate 33 and the lower surface of the conveyor belt 21 in the web forming area 23 is 180 mm.

[0076] Comparative Example 2

[0077] This embodiment is basically the same as Embodiment 3, except that:

[0078] The angle between the electrostatic plate 33 and the conveyor belt 21 of the web forming area 23 in S3 is 5°.

[0079] Comparative Example 3

[0080] This embodiment is basically the same as Embodiment 3, except that:

[0081] The static electricity is not discharged using the static electricity discharge component 5.

[0082] Comparative Example 4

[0083] This embodiment is basically the same as Embodiment 3, except that:

[0084] The reverse electrostatic device 3 is not used to apply a reverse electrostatic field.

[0085] Comparative Example 5

[0086] This embodiment is basically the same as Embodiment 3, except that:

[0087] The center line of the plane of the electrostatic plate 33 is not aligned with the vertical line of the screen 52, and deviates 20 mm to one side of the conveyor belt 21.

[0088] The screens prepared by the methods of Examples 1-5 and Comparative Examples 1-5 were subjected to the same hot pressing process to form polyethylene flash nonwoven fabrics, and then tested.

[0089] The test of hygroscopic expansion rate at relative humidity between 33% and 84% is carried out in accordance with the national standard GBT 22899.2-2008 Paper and paperboard, determination of hygroscopic expansion rate, part 2: hygroscopic expansion rate during the process of increasing the maximum relative humidity to 86%. Definition of hygroscopic expansion rate: The change in length of a sample of known length during the process of relative humidity equilibrium and increase from a specified lower value to a specified higher value. If shrinkage occurs, the hygroscopic expansion rate can be a negative value.

[0090] Geller air permeability is the time taken to pass 100 ml of gas. The national standard for the test is GBT 458-2008 Determination of air permeability of paper and paperboard.

[0091] The test process of gram weight, thickness and density is as follows: 50 samples are randomly selected from a sample of 10 square meters, of which the size of a single sample is 100mm*100mm; the gram weight is tested and the thickness is measured at the same time, and the thickness is measured three times and the average is calculated to obtain the thickness of this single sample. The density is calculated by the ratio of gram weight to thickness.

[0092] The specific test steps are:

[0093] (1) The thickness of 50 samples is classified into the above intervals according to [0.1 mm, 0.15 mm], (0.15 mm, 0.2 mm], (0.2 mm, 0.25 mm], (0.25 mm, 0.3 mm], and the number of samples distributed in different thickness intervals is obtained. Finally, the ratio of the number of samples belonging to (0.15 mm, 0.2 mm] to the total number of samples is taken as the ratio of the area of ​​polyethylene flash spun nonwoven fabric with a thickness between (0.15 mm, 0.2 mm] to the area of ​​all polyethylene flash spun nonwoven fabrics;

[0094] (2) Average the weights of 50 samples to obtain the weight of the sample;

[0095] (3) The thickness of the 50 samples is averaged to obtain the sample thickness;

[0096] The results are shown in Table 1 below:

[0097] Table 1 Test performance data table

[0098]

[0099] The letters of the table are:

[0100] A is the density, in g / m3;

[0101] B1 is the ratio of the area of ​​polyethylene flash-spun nonwoven fabric with a thickness in the range of [0.1 mm, 0.15 mm] to the area of ​​all polyethylene flash-spun nonwoven fabrics;

[0102] B2 is the ratio of the area of ​​polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] to the area of ​​all polyethylene flash-spun nonwoven fabrics;

[0103] B3 is the ratio of the area of ​​polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.2 mm, 0.25 mm] to the area of ​​all polyethylene flash-spun nonwoven fabrics;

[0104] B4 is the ratio of the area of ​​polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.25 mm, 0.3 mm] to the area of ​​all polyethylene flash-spun nonwoven fabrics;

[0105] C is the hygroscopic expansion rate (%) at relative humidity between 33% and 84%;

[0106] D is the Geller air permeability resistance, in seconds.

[0107] The results show that the present invention can improve the uniformity, Geller air permeability resistance and hygroscopic expansion rate of the product by adding a reverse electrostatic device at an appropriate distance, pre-discharging static electricity on the conveyor belt, and arranging electrostatic plates in parallel and opposite to each other.

[0108] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

[0109] Although the terms such as polyethylene flash spun nonwoven fabric, Geller air permeability resistance, spinning assembly, screen channel, nozzle, windshield, conveyor belt, web forming area, reverse electrostatic device, electrostatic generator, wire, electrostatic plate, electrostatic discharge assembly, discharge brush, discharge sheet fixing box, etc. are used more frequently in this article, these terms are used only to more conveniently describe and explain the essence of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A polyethylene flash-spun nonwoven fabric with uniform thickness, characterized in that: The raw material includes polyethylene, and the weight of polyethylene flash spun nonwoven fabric is greater than 50g / m 2 ; The thickness of the polyethylene flash-spun nonwoven fabric is 0.1-0.3 mm; the area of ​​the polyethylene flash-spun nonwoven fabric with a thickness in the range of (0.15 mm, 0.2 mm] accounts for more than 60% of the total area of ​​the polyethylene flash-spun nonwoven fabric; the hygroscopic expansion rate of the polyethylene flash-spun nonwoven fabric is 0.5%-0.8% at a relative humidity between 33% and 84%; The method for processing the polyethylene flash-spun nonwoven fabric with uniform thickness comprises the following steps: (1) The spinning solution is ejected through the nozzle, and the solvent in the spinning solution evaporates instantly. While the polymer solute in the spinning solution cools and solidifies into a continuous wire mesh, the steam formed by the evaporation of the solvent falls onto the conveyor belt in the web forming area together with the wire mesh under the guidance of the windshield; (2) The screen is adsorbed on the conveyor belt through the reverse electrostatic field of the reverse electrostatic device; (3) The screen is conveyed to the subsequent process section via a conveyor belt to obtain a polyethylene flash nonwoven fabric.

2. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The area of ​​polyethylene flash-spun nonwoven fabrics with a thickness in the range of (0.15 mm, 0.2 mm) accounts for more than 70% of the area of ​​all polyethylene flash-spun nonwoven fabrics.

3. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The area of ​​polyethylene flash-spun nonwoven fabrics with a thickness in the range of (0.15 mm, 0.2 mm) accounts for more than 80% of the total area of ​​polyethylene flash-spun nonwoven fabrics.

4. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The weight of polyethylene flash spun nonwoven fabric is 60-75g / m 2 .

5. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The weight of polyethylene flash spun nonwoven fabric is 75-85g / m 2 .

6. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The hygroscopic expansion rate of polyethylene flash-spun nonwoven fabric is 0.65% to 0.75% when the relative humidity is between 33% and 84%.

7. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The hygroscopic expansion rate of polyethylene flash spun nonwoven fabric is 0.7% when the relative humidity is between 33% and 84%.

8. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 1, characterized in that: The Geller air permeability resistance of polyethylene flash-spun nonwoven fabric is 10 to 50 seconds.

9. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 8, characterized in that: The Geller air permeability resistance of polyethylene flash-spun nonwoven fabric is 14 to 25 seconds.

10. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 8, characterized in that: The Geller air permeability resistance of the polyethylene flash spun nonwoven fabric is 20 seconds.

11. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 8, characterized in that: The Geller air permeability resistance of polyethylene flash-spun nonwoven fabric is 25 to 35 seconds.

12. A polyethylene flash-spun nonwoven fabric with uniform thickness as claimed in claim 8, characterized in that: The Geller air permeability resistance of polyethylene flash-spun nonwoven fabric is 35 to 45 seconds.

Citation Information

Patent Citations

  • Equipment for manufacturing uniform flash evaporation non-woven fabric

    CN218345645U

  • Composite fibrous polyethylene sheet

    US5013599A